Criptografia e esteganografia aplicadas a imagens digitais - Silva, João Paulo de Freitas Costa (Universidade Federal Rural do Semi-Árido, 2017)
Digital Image Processing, Encryption and Steganography can be combined to ensure the confidentiality of information. This paper proposes a process to add confidentiality to confidential information, arranged in the form of digital images. The process for adding confidentiality consists of two steps. The first is to encrypt the image. The second is to apply steganography. The Least Significant Bit Method with Rejection (LSBR) is a technique composed by a digital image encryption algorithm and a steganography algorithm, in which information arranged in the form of images can be camouflaged in other images. The main objectives of this work are to present the LSBR as a proposal of steganography for digital images, besides comparing this technique with the LSB Replacement and LSB Matching methods. In order to compare these methods, a set of tests was performed, in which quality metrics for digital images such as MSE, PSNR and Entropy were evaluated. A repository was used to obtain the images that participated in the tests and these images were separated into the sets of cover images and secret images. Each test was performed by applying the methods under analysis, incorporating images of one group into images of the other. The results of each of the tests were then compared. The LSBR method proved to be superior to the other two methods in the histogram perceptual evaluation and in the entropy analysis, besides presenting good results for the PSNR analysis.
Keywords: LSB com Rejeição; LSB Matching; LSB Replacement; Esteganografia; Criptografia; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO